Interactions of Escherichia coli RNA with bacteriophage MS2 coat protein: genomic SELEX - Shtatland, Timur (Oxford University Press, 2000)
Genomic SELEX is a method for studying the network of nucleic acid–protein interactions within any organism. Here we report the discovery of several interesting and potentially biologically important interactions using genomic SELEX. We have found that bacteriophage MS2 coat protein binds several Escherichia coli mRNA fragments more tightly than it binds the natural, well-studied, phage mRNA site. MS2 coat protein binds mRNA fragments from rffG (involved in formation of lipopolysaccharide in the bacterial outer membrane), ebgR (lactose utilization repressor), as well as from several other genes. Genomic SELEX may yield experimentally induced artifacts, such as molecules in which the fixed sequences participate in binding. We describe several methods (annealing of oligonucleotides complementary to fixed sequences or switching fixed sequences) to eliminate some, or almost all, of these artifacts. Such methods may be useful tools for both randomized sequence SELEX and genomic SELEX.